Dilemas éticos en el proceso de investigación - Schramm, Christina (2013)
This article will discuss some of the ethical dilemmas in ethnographic investigation. In recognition of the complexity of intersubjective relationships between those who investigate and those who are investigated, it is sought a stimulation for a stronger critical reflection on how these relationships influence in the process of scientific works.